2019
DOI: 10.1080/15384101.2019.1637202
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of AQP1 silencing on adhesion and angiogenesis in ectopic endometrial cells of mice with endometriosis through activating the Wnt signaling pathway

Abstract: The development mechanism of endometriosis remains unknown. Water channel aquaporin-1 (AQP1) enhances water flux across cell membranes, which is highly expressed and associated with cell migration, metastasis and angiogenesis in some human cancers. In this study, the role of the Wnt signaling pathway mediated by AQP1 in endometriosis was investigated, in a bid to provide new therapeutic targets for endometriosis. Microarray expression profiles were screened to acquired differentially expressed genes related to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Water channel protein-AQP1 maintains the osmotic balance in the renal cells and associates with cell migration and angiogenesis (32). Recently adequate evidence supported that inhibition of AQP1 relates to impaired migration, invasion and tubulogenesis in vitro (33). We have shown AQP1 knockdown inhibited cell migration and tube formation that was enhanced by SQW administration.…”
Section: Discussionmentioning
confidence: 76%
“…Water channel protein-AQP1 maintains the osmotic balance in the renal cells and associates with cell migration and angiogenesis (32). Recently adequate evidence supported that inhibition of AQP1 relates to impaired migration, invasion and tubulogenesis in vitro (33). We have shown AQP1 knockdown inhibited cell migration and tube formation that was enhanced by SQW administration.…”
Section: Discussionmentioning
confidence: 76%
“…In addition, aquaporins also seem to have an important role in endometriosis. Shu et al observed that silencing of AQP1, which is upregulated in endometriosis disease, induces the activation of the Wnt signaling pathway that results in a decreased adhesion, invasion, and in the induction of apoptosis of ectopic cells [ 89 ].…”
Section: Channels-wnt-dependent Signaling Axes In Diseasesmentioning
confidence: 99%
“…AQP1 might have a role in endometriosis via the Wnt/β-catenin signaling pathway. Hence, AQP1 gene silencing entails a decrease in the adhesion and invasion of ectopic endometrial cells, as well as a decrease in angiogenesis and an increase in the apoptosis rate of these cells [ 149 ]. In the same way, AQP5, whose expression is menstrual cycle-dependent [ 150 ], is more highly expressed in eutopic as compared with ectopic endometrial cells in women with endometriosis [ 151 ].…”
Section: Aquaporins In Endometriosismentioning
confidence: 99%
“…Their involvement in several intracellular signaling pathways as signal regulating factors (via transporting molecules or coupling with other proteins) [ 159 ] should be taken into account. Particularly, AQPs 1, 2, 8, and 9 could be related to endometriosis due to their participation in different signaling pathways such as Wnt/β-catenin, ERK/p38 MAPKm, and PI3K/Akt [ 149 , 152 , 154 ]. Hence, more studies are needed to reveal the actual signaling regulatory function of AQPs.…”
Section: Aquaporins In Endometriosismentioning
confidence: 99%